Obtenção de variabilidade genética em aveia preta (Avena strigosa Schreb) por meio de agentes mutagênicos químicos - Baretta, Douglas Rodrigo (2018)
Consolidated as the main source of winter forage in the temperate regions of Brazil, the genus Avena sp., mainly Avena strigosa Schreb. (black oats), occupy areas from northern Paraná to the southern end of Rio Grande do Sul. However, there is a low availability of black oat cultivars, since the genetic progress obtained by the research institutions, when compared to large crops, is minimal due to difficulties in promoting genetic rearrangements. Operational and morphological limitations in artificial hybridization and low germination are negative determinants. With the objective of promoting increased genetic variability through the induction of mutations, two chemical mutagenic agents, EMS (ethyl methanesulfonate) and MMS (methyl methanesulfonate) were used on a fixed black oat genotype at different concentrations. Deleterious and beneficial effects on plant stature characteristics (EST), such as flowering emergence days (DEF), total dry matter (MS), grain mass (MG), and harvest index (IC), were measured over two generations M1 and M2. The results demonstrated the efficiency of both the tested mutagens in generating plants that had phenotypic characteristics that were divergent from the original genotype. Variations in qualitative characters such as seed color and plant architecture could be observed in the evaluations. The mutagenic agents EMS and MMS, at the concentrations of 3% and 0.75% respectively, were efficient enough to generate mutants of black oats for the characters: DEF, EP, MS, MG and IC.